Perspectives for global trade and the international trading system - Alexander Keck; John Hancock; Coleman Nee (Wirtschaftsdienst, 2018)
The authors review current developments in international trade and its prospects for the future arguing that despite the recent slowdown, trade remains an important driver of economic growth and development. Scepticism towards further trade opening needs to be addressed, notably via appropriate domestic adjustment policies. One challenge to advancing further global economic integration lays in the rapid transformation of trade itself and the nature of remaining barriers. The authors highlight new models of trade cooperation that can help to make progress at the global level, while accommodating countries' diverse interests and levels of development.
Keywords: F13; F14; F17; 330